2013
DOI: 10.1590/s0103-84782013000800027
|View full text |Cite
|
Sign up to set email alerts
|

Cinética da degradação de carotenoides e da alteração de cor do azeite de pequi submetido ao aquecimento em temperatura de fritura

Abstract: O azeite de pequi possui coloração vermelho-alaranjada devido à presença de carotenoides. Possíveis alterações químicas nesses compostos durante o processamento podem influenciar em modificações físicas do produto que ocorrem quando este é submetido ao aquecimento. Este estudo teve como objetivo utilizar parâmetros cinéticos para avaliar a degradação de carotenoides e a alteração de cor do azeite de pequi submetido ao aquecimento em temperatura de fritura. Para avaliar o efeito do aquecimento, o azeite de pequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
3
0
5
Order By: Relevance
“…In addition, important fat-soluble pigments are dispersed in this oily fraction, such as carotenoids, which represent a total of 32.18 mg g -1 in the pequi pulp according to L. G. . According to M. L. Rodrigues, Souza, Lima, Moura and Geraldine (2013), pequi oil at a temperature of 180 °C has low loss of carotenoids in short frying times, such as the four minutes used for cooking breaded in this study, which is why it is suggested that a large amount of carotenoids were preserved in the breaded produced.…”
Section: Chemical Compositionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, important fat-soluble pigments are dispersed in this oily fraction, such as carotenoids, which represent a total of 32.18 mg g -1 in the pequi pulp according to L. G. . According to M. L. Rodrigues, Souza, Lima, Moura and Geraldine (2013), pequi oil at a temperature of 180 °C has low loss of carotenoids in short frying times, such as the four minutes used for cooking breaded in this study, which is why it is suggested that a large amount of carotenoids were preserved in the breaded produced.…”
Section: Chemical Compositionmentioning
confidence: 69%
“…These results regarding coloring reveal that the presence of PPF chromogenic compounds determined a more intense color on the outside of the breaded, so as the addition of pequi increased, the samples had more color pigments between red and yellow, that is, possibly because of the richness of the carotenoids present in the fruit (Cardoso et al, 2013;Mendonça et al, 2017;M. L. Rodrigues et al, 2013;Saxena, Maity, Raju, & Bawa, 2012).…”
Section: Table 3 Results Of the Analysis Of Volume Yield And Color Omentioning
confidence: 85%
“…Comportamento semelhante foi observado para a alteração da cor do azeite de pequi, que seguiu a cinética de ordem zero (Rodrigues et al, 2013). Porém, vários estudos relataram que a degradação da cor em temperaturas até 100 o C durante o processamento de alimentos ou durante o armazenamento segue um modelo cinético de primeira ordem: xarope de morango (Skrede et al, 1992), suco concentrado de cenoura preta (Türkyilmaz e Özkan, 2012); com valores dos coeficientes de determinação variando de 0,68 a 0,91.…”
Section: Luminosidadeunclassified
“…As atividades benéficas de produtos feitos utilizando o pequi para o organismo pode ser reduzida, caso haja exposição ao calor, oxigênio, acidez alta, luz e baixa atividade de água (RODRIGUES, 2013).…”
Section: Caryocar Brasiliense Cambunclassified